2008
DOI: 10.1016/j.ijdevneu.2008.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Chronic developmental exposure to phenytoin has long‐term behavioral consequences

Abstract: Anti-epileptic compounds have been linked to several developmental disorders. Specifically, fetal exposure to phenytoin is linked to fetal hydantoin syndrome in humans. We have developed a rat model of fetal hydantoin syndrome in an effort to explore the relationship between drug exposure, development, and learning and memory. Previous studies of this animal model have used various embryological periods of exposure; however, the human syndrome is reported in the offspring of mothers that maintain drug regimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…Similar findings have been reported in Sprague Dawley ® rats (Mowery et al ., 2008). However, another report indicated that phenytoin administration at early-postnatal stages reduced food intake and weight gain (Mowery et al ., 2008).…”
Section: Discusionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar findings have been reported in Sprague Dawley ® rats (Mowery et al ., 2008). However, another report indicated that phenytoin administration at early-postnatal stages reduced food intake and weight gain (Mowery et al ., 2008).…”
Section: Discusionsupporting
confidence: 91%
“…However, another report indicated that phenytoin administration at early-postnatal stages reduced food intake and weight gain (Mowery et al ., 2008). These changes were reversible when phenytoin supplementation was suspended or when administrated at older development stages (Mowery et al ., 2008; Okada et al ., 2001; Okada et al . 1997).…”
Section: Discusionmentioning
confidence: 99%
“…More recently, studies have been conducted in which the maternal rat was exposed to phenytoin for the duration of the pregnancy and pre-weaning period to more closely resemble a human mother’s experience of taking the medication throughout pregnancy and nursing. Higher order learning in which rats transitioned from appetitive (positive reinforcement) to aversive conditioning was impaired (Mowery et al, 2008), and the authors suggested a mechanism of impaired hippocampal development, which has been seen histologically in mice and rats exposed to phenytoin and other AEDs perinatally (Ogura et al, 2002; Vorhees et al, 1990). …”
Section: Animal Studiesmentioning
confidence: 99%
“…This paradigm was developed to study appetitive and aversive learning in the same subjects, and has been used in past work to evaluate learning, memory, and impairments that accompany cerebellar, hippocampal, cingulate, and prefrontal cortex lesions (Steinmetz et al, 1993; Logue, 1994). We have used this behavioral paradigm to evaluate the effects of phenytoin and carbamazapine in adult rats (Banks et al, 1999, 2001; McDowell et al, 2004), rats exposed to phenytoin in utero (Mowery et al, 2008), rats with lesions of the basal nucleus of Meynart (Butt et al, 2003), ovariectomized female rats with or without estradiol replacement (Goodman et al, 2004), and rats undergoing chronic restraint (McDowell et al, 2013). …”
Section: Introductionmentioning
confidence: 99%